Determinants of Japanese Household Saving Behavior in the Low-Interest Rate Environment - Sophia Latsos; Gunther Schnabl (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper scrutinizes the role of prolonged, expansionary monetary policy on the savings behavior of Japanese households, focusing on the dramatic change of the household savings rate since 1998, from high to low savings. The literature generally attributes this change to the country's shift from high-growth to low-growth and its demographic change. This paper empirically examines changes in the incentives for saving and the ability to save connected to monetary policy. It finds that monetary policy had a significant impact on Japan's household behavior via the interest rate channel and the redistribution channel but not the labor income channel. There is also evidence that rising wealth boosts savings.
Keywords: E21; E43; E52; 330; monetary policy; household savings; savings rate; Japan; financial repression